Food price inflation in India: The growing economy with sluggish agriculture - Joydeb Sasmal (Journal of Economics, Finance and Administrative Science, 2015)
India is experiencing high rate of economic growth in the last two decades but the growth has been coupled with high rate of food price inflation. The growth has been very uneven across sectors with agriculture remaining very sluggish. The increase in per capita income has significantly increased the demand for food but agricultural production has failed to keep pace with the growing demand. The theoretical explanations and time series econometric results establish that increase in per capita income and shortage in supply are responsible for price rise. There is no long run relationship between money supply and agricultural price. Increasing public expenditure and unfavorable foreign exchange rate have some effects on price although the results are not robust. – – India está experimentando un elevado índice de crecimiento económico en las últimas dos décadas, aunque dicho crecimiento ha ido acompa\~nado de una elevada tasa de inflación de los precios de los alimentos. Este aumento se mostró bastante desigual entre los diferentes sectores, siendo muy lento en el sector agrícola. El incremento de la renta per cápita ha elevado considerablemente la demanda de alimentos, pero la producción agrícola no ha seguido el ritmo del crecimiento de la demanda. Las explicaciones teóricas y los resultados econométricos de las series de tiempo establecen que el incremento de la renta per cápita y la escasez de los suministros son los causantes del alza en los precios. No existe una relación a largo plazo entre el suministro dinerario y los precios agrícolas. El aumento del gasto público y las tasas poco favorables del cambio de divisas tienen ciertos efectos sobre los precios, aunque los resultados no son sólidos.
Keywords: E31; 330; Economic growth; Per capita income; Growing demand; Food grains production; Public expenditure; Shortage; Price rise; Crecimiento económico; Renta per cápita; Crecimiento de la demanda; Producción de cereales para alimentación; Gasto público; Escasez; Incremento de los precios